Priapism in chronic myeloid leukemia: Meeting at the crossroads and heading in different directions - Kundan Mishra; Aditya Jandial; Vikram Singh; Bishan Das Radotra; Pankaj Malhotra (Indian Journal of Medical and Paediatric Oncology)
Chronic myeloid leukemia (CML) is the most common leukemia presenting with priapism. Due to social stigma or shyness, the real incidence of priapism in our population is difficult to estimate. Since the successful development of tyrosine kinase inhibitors, the life expectancy of CML-chronic phase (CML-CP) has been comparable to the healthy population, and the importance of priapism has further magnified. As of now, the long-term outcome and fertility issues are not very well known. We present the case of a 24-year-old previously healthy gentleman who presented with priapism and was diagnosed as CML-CP. He achieved major molecular response at 18 months. On follow-up at 2 years since the diagnosis, he offers no complaint except moderate erectile dysfunction (International Index of Erectile Function score 11), compromising his quality of life.